PENGARUH DIGITAL INFLUENCER DAN DISKON TERHADAP MINAT BELI ULANG DALAM E-COMMERCE - Abimanyu Bramasta; Irmawati Irmawati (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
In the digital era, there is a new view of business life, namely with online trading sites or platforms (e-commerce). This requires business people to transform conventional trading systems into modern systems, this modern trading system allows businesses to cover a wider market than conventional trading systems. This study aims to analyse the effect of Digital Influencers and Discounts on Repurchase Interest in E-commerce in Surakarta city with Brand Image as an intervening variable. The population in this study was conducted on students in the city of Surakarta who had bought in e-commerce. The sample in this study consisted of 100 respondents taken from the Partial Least Square (PLS) based Purposive Model Technique (SEM) with the help of SmartPLS software. The results of the study found that: (1) Digital Influencers have a positive and significant effect on Repurchase Intention in E-commerce. (2) Discount has a positive and significant effect on Repurchase Interest in E-commerce. (3) Brand Image has a positive and significant effect on Repurchase Intention in E-commerce. (4) Brand Image plays a role in mediating the influence of Digital Influencers on Repurchase Intention in E-commerce. (5) Brand Image plays a role in mediating the effect of Discount on Repurchase Intention in E-commerce. Keywords: Discount, E-Commerce, Influencer, Repurchase Intention